دورالإعلام في تطوير البحث في الإقتصاد الإسلامي - Ø¹Ø¨Ø¯ Ø§Ù„ØØ§ÙØ¸ Ø§Ù„ØµØ§ÙˆÙŠ (Millah: Journal of Religious Studies, 2009)
This paper addressed the role of  media in the development of  research in Islamic Economics, taking off  through the fact  that both flags from  the social sciences and the impact each other and  are influenced by informed historical juncture in which we live globalization paper focuses on the concept of  positive information which is based on the theory of  social responsibility with an analytical reading of  the theories other information and  the extent to which the area of  research with reference to the reality of  Islamic Economics, development, and focus on experienced in research, in particular, the paper also came to the nature of  the relationship between the media and Islamic economy through the reality of  Islamic Economics in the media and concludes the paper to know the aspects of Algosorvi both sides and put  the requirements of  must be entered into the real world so that there is a positive relationship is achieved in which a role for  media  in the development of  research in Islamic Economics.